Relation Between Glycated Hemoglobin Level and Hearing Loss in Type 2 Diabetic Patients - Mayada ElSherif; Aya Fathey El Sayed Mahfouz; Noha Mohamed Gaber Amin; Hesham Saad Kozou (Journal of International Advanced Otology)
Background: Glycemic control and the efficacy of therapy in diabetic patients with type 2 diabetes during the previous 2-3 months are usually evaluated by measuring the glycated hemoglobin (HbA1c). Our aim is to study the correlation between serum glycated hemoglobin level (HbA1c) and the hearing thresholds in diabetic patients.